Understanding Reflective Practice through Reflective Levels and Training Pathway Characteristics - Xu, Rui; Goh, Pauline Swee Choo; Yunus, Hashimah Mohd (International journal of instruction, 2025)
Reflective practice is widely recognized as a fundamental aspect of teacher development, but its practical implementation often poses challenges for pre-service teachers. Although essential for professional growth, the depth and nature of reflective practice vary considerably among pre-service teachers. This study investigates the reflective practices of Chinese pre-service teachers during their education internships, examining how training pathway characteristics-qualification, teaching grade level, teaching experience, and teaching certification-influence their levels of reflective practice. Grounded in Larrivee’s (2008) framework, this quantitative study surveyed 198 pre-service teachers using a validated instrument for measuring levels of reflective practice. The findings reveal notable patterns: pre-service teachers most frequently engage in critical and pedagogical reflection, while surface and pre-reflection levels are comparatively less common. Specifically, qualification is associated with deeper levels of reflection; teaching grade level affects pre-reflection and surface reflection; and teaching experience significantly shapes critical reflection. Additionally, obtaining a teaching certification is linked to heightened pre-reflection and surface reflection. These results underscore the complexity of reflective practice and its interaction with pre-service teachers’ training pathway characteristics. The study offers insights for teacher educators seeking to understand reflective practice and to design targeted interventions that foster reflective capacity. By clarifying the relationship between levels of reflection and training pathway characteristics, this research contributes to the advancement of teacher preparation in the Chinese context.